Controllable synthesis and change of emission color from green to orange of ZnO quantum dots using different solvents. (12th February 2015) - Liu, Xu; Xing, Xinxin; Li, Yuxiu; Chen, Nan; Djerdj, Igor; Wang, Yude
Abstract : ZnO quantum dots, a few nanometers in size, exhibited strong visible emission from green to orange, resulting from the quantum size effect and the change in defect concentration due to the different solvents used for preparation. Abstract : ZnO quantum dots (QDs), a few nanometers in size, were synthesized by a sol–gel method using different solvents (methanol, ethanol and hexanol). The structural, morphological and photoluminescent properties were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), photoluminescence spectrometry, and UV-vis spectroscopy. The results indicated that ZnO QDs with good dispersion, ranging in size from 3.3 nm to 7.7 nm, could be controlled easily by the solvents. The ZnO QDs exhibited strong visible emission from green to orange. The reasons for the change in emission color are believed to be the quantum size effect and the change in defect concentration due to the different solvents used in their preparation. A possible mechanism for the photoluminescence of ZnO QDs is also presented.